Moderation and Envisioned Civilization: The Interplay Between Rationality, Morality, Spirituality - Abdullah, Mujaddid bin (Al-Wasatiyah: Journal of Religious Moderation, 2024)
The triumph of Western civilization which marked bysignificant industrial revolution through scientific breakthroughs andtechnological advancements still not necessarily make this civilizationbetter as expected. With strongly emphasis on its pursuit ofrationality, this civilization has faced criticism from numerousexperts due to its various deficiencies and subsequent detrimentalconsequences. This article will investigate on how the notion of"envisioned civilization" can be realized by starting the process of itsformation on the principle of moderation. The existence ofmoderation in the context of envisioning a civilization lies whencivilization is driven by synthesizing Rationality, Morality andSpirituality in a balanced manner and taking roles for each other.Based on interdisciplinary approach, the study examines how theseamless incorporation of logical reasoning, ethical standards, andspiritual beliefs might enhance the development of a well-roundedand enlightened social structure. The findings demonstrate that byintegrating these three dimensions harmoniously can support thelimitation of rationality aspect, establishing a more comprehensivecivilization